(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In this paper studied isometries of F −spaces of integrable functions with logarithm. In particular, using passports of Boolean algebra, a necessary and sufficient condition of isometry F −spaces of integrable functions of logarithm with respect to strictly positive  −finite measures is proved.In this work generalized log− algebras are considered separately.